CGIAR Platform for Big Data in Agriculture - Plan of Work and Budget 2018 - CGIAR Platform for Big Data in Agriculture (CGIAR Platform for Big Data in Agriculture, 2018)
This Plan of Work and Budget (POWB) for 2018 includes chapters on the following: 1) expected key results, 2) planning for platform effectiveness and efficiency, and 3) platform management. There are also a number of tables at the end, relating to planned milestones, expected outputs, budget, partnerships, collaborations, monitoring, risks to performance, mitigation strategies, and indicators or targets.